Effects of Occupational Silica Exposure on OXIDATIVE Stress and Immune System Parameters in Ceramic Workers in TURKEY. Issue 13 (3rd August 2017) - Anlar, Hatice Gul; Bacanli, Merve; İritaş, Servet; Bal, Ceylan; Kurt, Türker; Tutkun, Engin; Hinc Yilmaz, O.; Basaran, Nursen
ABSTRACT: Silica is the second most common element after oxygen, and therefore, exposures to crystalline silica dust occur in a large variety of occupations such as metal foundries, constructions, and ceramic, quarry, and pottery industries. Since crystalline silica exposure has been linked with silicosis, lung cancer, and other pulmonary diseases, adverse effect attributed to this element has be a cause for concern worldwide. Silica dust exposure in workers is still considered to be important health problem especially in developing countries. The aim of the study was to investigate the effects of occupational silica exposure on oxidative stress parameters including the activities of superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx), and levels of total glutathione (GSH) and thiobarbituric acid reactive substance (TBARS) as well as immune system parameters such as interleukin (IL)-1α, IL-1β, IL-2, IL-4, IL-6, and IL-10 and tumor necrosis factor (TNF)-α in Turkish ceramic workers. In this study, nearly 50% of Turkish ceramic workers were diagnosed with silicosis. Eighty-four percent of these silicotic workers were found to present with profusion category 1 silicosis, whereas controls ( n = 81) all displayed normal chest radiographs. Data demonstrated a significant decrease in levels of GSH and activities of CAT, SOD, and GPx, but a significant increase in MDA levels and activity of GR in all workers. Further, workers possessed significantly higher levels of IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, and TNF-α. These observations suggest that ceramic workers may have impaired antioxidant/oxidant status and activated immune system indicative of inflammatory responses.